The Relationship Between Digital Literacy and The Competency of Prospective Teacher Students in The Society 5.0 Era - Mahmud, Muhammad Rifqi; Ekawati, Dian (PrimaryEdu : Journal of Primary Education, 2023)
The emergence of society 5.0 promotes balance in all fields, especially education, and can provide a role in the progress of the learning process. The importance of students having digital literacy skills and competencies of prospective teachers is to have a critical and creative mindset for learning innovation in the classroom and be able to process information wise. The purpose of  this study is to see the ability of digital literacy and the competence of prospective teacher students and find out the influence of digital literacy on the competence of prospective teacher students in the era of society  5.0. The research uses a quantitative approach with a correlation method. The research population was all students of the Faculty of Tarbiyah and Teacher Training UIN Sunan Gunung Djati, with a sample of 1.132 students. The sampling technique uses random sampling. Data is collected through filling out questionnaires. The results of this study show that students are ready to face the era of society 5.0, marked by students being good at operating the internet to find  information and balanced by understanding the competence of the prospective teacher. There was a significant positive relationship between digital literacy and the competence of prospective teacher students and obtained an r count of 0.645 in the high category. It is shown that 41.6% of the competencies of prospective teachers are influenced by digital literacy and other unrelated factors with this study influence the remaining 58.4%.